Chemical and Topological Control of Surfaces Using Functional Parylene Coatings - Mohammadi Hafshejani, Tahereh; Zhong, Xiaoyang; Kim, John; Dadfar, Bahar; Lahann, Joerg (Organic Materials, 2023)
Chemical vapor deposition (CVD) polymerization is a prevalent technique for fabricating conformal, defect-free, and systematically adjustable organic thin films. CVD is particularly beneficial for barrier coatings due to its ability to eliminate solvent-related environmental, health, and safety risk factors and provide a wide spectrum of post-polymerization modification strategies. This review discusses poly-p-xylylene and its functional derivatives. CVD polymerization of [2.2]paracyclophane precursors has undergone a recent renaissance due to advancements in chemical and morphological surface manipulation. This review summarizes emerging trends based on the following outline:Table of content:1 Introduction2 CVD Polymerization as a Sustainable Coating Technology3 CVD Instrumentation4 Poly-p-xylylene Coatings: Background of Polymerization Process and Functionalized Films5 Main Applications of Poly-p-xylylenes6 Area-Selective CVD Polymerization7 Fabrication and Applications of Topological Structures8 Conclusions and Outlook
Keywords: CVD polymerization; biointerfaces; area-selective deposition; multifunctional interfaces; surface engineering